PENDIDIKAN ISLAM HOLISTIK DAN KOMPREHENSIF - Zainal Azman (Edification Journal : Pendidikan Agama Islam, 2019)
Holistical comprehensive education can be built on a religious norm, psychology, culture, philosophy, management and Tasawwuf. Islam as a universal and true religion contains human aspect, philosophy,that has a deep, systematical, radical, universal, comprehensive and holistical thought, which suits on religious values, has a strategical position, provides huge portion of teaching in building an educational and holistical comprehensive education.In Indonesia, holistical comprehensive education is not studied deeply, whereas, there are still many problems on education that need to be solved. Therefore, this study is more focused on the religion, and philosophy, related with holistical educational design that should be done sustainably.